2010
DOI: 10.1002/uog.7504
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic assessment of fetal spine and head position during the first and second stages of labor for the diagnosis of persistent occiput posterior position: a pilot study

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 18 publications
1
52
1
2
Order By: Relevance
“…Blasi et al [6] showed that the diagnostic sonographic accuracy of the foetal occiput position assessment at the second stage of labour had a sensitivity of 100%, specificity of 78%, positive predictive value (PPV) of 26%, and negative predictive value (NPV) of 100% to predict the same position at birth. Considering the foetal spinal position, ultrasound showed a sensitivity of 100%, specificity of 98%, PPV of 85%, and NPV of 100% [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blasi et al [6] showed that the diagnostic sonographic accuracy of the foetal occiput position assessment at the second stage of labour had a sensitivity of 100%, specificity of 78%, positive predictive value (PPV) of 26%, and negative predictive value (NPV) of 100% to predict the same position at birth. Considering the foetal spinal position, ultrasound showed a sensitivity of 100%, specificity of 98%, PPV of 85%, and NPV of 100% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the foetal spinal position, ultrasound showed a sensitivity of 100%, specificity of 98%, PPV of 85%, and NPV of 100% [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most occiput posterior positions at delivery are the initial occiput posterior position rather than misrotation from an original occiput anterior or transverse position [5,6]. Several recent studies support this notion of POPP as the main cause of occiput posterior delivery, although the concept of malrotation of the initial occiput anterior or transverse position for POPP prevailed even until approximately a decade ago [5,7,8]. …”
Section: Fetal Head Positionmentioning
confidence: 99%
“…Blasi et al [7] suggest that the positions of the head and spine during the second stage of labor could be practical indicators for predicting the occiput posterior position at delivery. In their prospective cohort study, 100 singleton pregnant women underwent intrapartum ultrasound during the first and second stages of labor, and the positions of the fetal head and spine were defined.…”
Section: Fetal Head Positionmentioning
confidence: 99%
“…Blasi et al [5] have shown in a pilot study that the final head positions in labor can be predicted by following the spine and head position during the second stage of labor. The authors showed that if the fetal back was posterior at the second stage of labor and the fetal head position was OP, the head would probably not rotate to OA position during delivery.…”
Section: Introductionmentioning
confidence: 99%